Chikungunya virus infection in the skin: histopathology and cutaneous immunological response - Salomão, Natália Gedeão; Araújo, Luciana; de Souza, Luiz José; Luiza Young, Anna; Basílio-de-Oliveira, Carlos; Basílio-de-Oliveira, Rodrigo Panno; de Carvalho, Jorge José; Nunes, Priscilla Conrado Guerra; da Silva Amorim, Juliana Fernandes; Barbosa, Douglas Valiati dos Santos; Paes, Marciano Viana; Rabelo, Kíssila; et al. (Frontiers in Microbiology, 2025)
Alphavirus chikungunya virus (CHIKV) is an arbovirus, belonging to the Togaviridae family. The disease caused by CHIKV generally evolves with spontaneous resolution in a few weeks; however, progression to a chronic disease may occur. The most common symptoms are fever, myalgia, and arthralgia; however, skin manifestations may occur in 40 to 80% of infected individuals. Morbilliform and maculopapular erythematous eruptions, vesiculobullous lesions, generalized erythema, maculopapular eruption and skin peeling, hypermelanosis, painful oral lesions, and urticarial lesions have been reported. Usually, these manifestations disappear, but they can become sequelae. Since the skin is the first line of defense against CHIKV infection, in this study, we aimed to investigate the immunohistopathological aspects of the skin of infected individuals during the acute phase of the disease by performing histopathological and ultrastructural analysis, detection and quantification of the viral genome, detection of viral antigen and immune cells, and cytokines/chemokines’ characterization. The main histopathological findings were perivascular and inflammatory infiltrates, blood capillary ectasia, and interstitial edema. The immunohistochemistry revealed CHIKV antigen in the epidermis, endothelial cells, fibroblasts, and macrophages in the reticular and papillary dermis; inflammatory cells infiltrate; arrector pili muscle; sweat and sebaceous glands; and hair follicle. Moreover, inflammatory infiltrates were composed of lymphocytes (CD4+ and CD8+) and macrophages (CD68+) in the dermis and perivascular infiltrate. TNF-α, IL-6, RANTES, and VEGFR2 were expressed in the epidermis, blood vessels, sweat glands, and migrating cells. Loss of contact among adjacent keratinocytes, epidermis presenting necrotic cells, and fibroblasts with dilated cisternae in the endoplasmic reticulum and mitochondria with few cristae was observed by transmission electron microscopy. Studies involving skin immunopathogenesis during CHIKV infection are still scarce; therefore, the findings presented here can contribute to a better understanding of the disease immunopathogenesis.